Estimation of erosion risk of Harebakayiş sub-watershed, Elazig, Turkey, using GIS based RUSLE model - Gürtekin, Engin; Gökçe, Oğuz (Elsevier B.V., 2021)
In this study, erosion risk analysis of Harebakayış sub-watershed of Elazig, Turkey was evaluated using RUSLE model based on GIS. In order to make calculations in the RUSLE model, data obtained from soil maps, meteorology station and satellite images were used. The maps of the factors in the RUSLE were integrated in ArcGIS 10.4.1 and soil erosion rate was calculated. High erosion risk was estimated as 68%, 70% in grasslands, sparse forest, respectively. The results indicated that while the erosion risk was high in 43.2% of the sub-watershed, in the section of 56.8% was normal and lower. It had been determined that regions with high erosion were located in the western part of the sub-watershed. The high risk of erosion in this region is due to the land's steepness and lack of vegetation. © 2021
Keywords: GIS; Harebakayış sub-watershed; RUSLE; Soil loss